Green materials from plant oils - Liu, Zhengshe; Kraus, George (Royal Society of Chemistry, 2015)
This book covers the synthesis of useful products and intermediates from plant oils, which is a critically important area given current challenge of depleting fossil fuel reserves.
Includes index.
Title from content provider.
Keywords: Vegetable oils.; Green chemistry.; elektronické knihy; electronic books